PENGUATAN KESADARAN HUKUM MASYARAKAT MELALUI MODEL PELATIHAN DAN PENYULUHAN PARTISIPATIF - Roni Sahindra; Dermina Dalimunthe; Muannif Ridwan (Yayasan Baitul Hikmah al-Zain, 2026)
This community service program aims to enhance legal awareness among local communities through a participatory training and counseling model. The initiative was prompted by the low level of public understanding regarding legal rights and obligations, as well as the prevalence of regulatory violations due to limited knowledge. The program was implemented using a field-based approach, beginning with needs analysis, formulation of relevant legal materials, and followed by interactive training sessions and open counseling activities. The methods employed included lectures, group discussions, case studies, and simple simulations to facilitate community understanding of common legal issues, such as land disputes, debt agreements, and family-related matters. The outcomes indicate an improvement in legal comprehension, demonstrated by active community participation in discussions and their ability to identify appropriate legal solutions in accordance with applicable regulations. Furthermore, the program strengthened relationships between the community and village authorities acting as legal facilitators. Through training and counseling, participants became more confident in addressing legal issues and committed to complying with regulations. The findings demonstrate that participatory training and counseling serve as effective instruments for fostering legal awareness and supporting the development of a law-abiding culture at the local level.